Antioxidant and Antivenom Potential of an Essential Oil, 4-(2-Oxo-propyl)-cyclopentane-1, 3-dione, and Allantoin Derived from the Polyherbal Combination of Aristolochia indica L. and Piper nigrum L. (7th March 2022) - Sivaraj, Dhivya; Butcher, Ray J.; Jasinski, Jerry P.; Sathyanarayanan, Saikumar; Ponnusamy, Revathi; Sasidharan, Sreeja Puthanpura; Muniyandi, Kasipandi; Thangaraj, Parimelazhagan; Arunachalam, Karuppusamy
Abstract : The goal of this study was to identify new compounds from a methanol extract of a polyherbal combination of Aristolochia indica L. and Piper nigrum L. (MECAIPN), two traditional medicinal plants used to cure envenomation, as well as to assess their antioxidant and antivenom properties. MECAIPN yielded EA1 (an essential oil), AA2 (4-(2-oxo-propyl)-cyclopentane-1, 3-dione), and W3 ((2, 5-dioxo-imidazolidin-4-yl)-urea) (Allantoin). Although EA1 had stronger radical scavenging activity, AA2 had higher DPPH and ferric ion radical scavenging activity, and W3 had higher molybdenum ion radical scavenging activity due to being a single molecule, the binding investigation revealed that EA1 has a greater Stern–Volmer quenching constant (Ksv) than AA2 and W3. Synchronous measurements indicated that EA1, AA2, and W3 bind to tryptophan and tyrosine residues in venom, causing denaturation of the secondary structure of the residue. Finally, the current study concludes that EA1 has more therapeutic antivenom potential, which could be related to the synergism of chemicals found in it. When it came to single compounds, AA2 had stronger antioxidant and antivenom capabilities than W3. To understand the mechanism of action and manufacture the green antivenom medication, more testing of the EA1 and compounds remains required.